Attitudes à l’égard de la langue bretonne - Marcel Benot (La Bretagne Linguistique, 1987)
I conducted a survey in Milizac by submitting a questionnaire to a sample of the population. The elements I report on below are those that came to me, depending on the direction of my immediate curiosity, when I began to exploit the responses. While they bear witness to the variety of attitudes towards Breton, they allow me to make a few observations and point to possible directions for further research and analysis.